Pengembangan Literasi Digital Di Kalangan Guru Dan Siswa: Kajian Pustaka - Leli Hasanah Lubis; Budi Febriani; Meisa Fitri Nasution; Usmala Dewi Siregar; Agus Salim (Tarbiyah bil Qalam : Jurnal Pendidikan Agama dan Sains, 2025)
The rapid advancement of information and communication technology has brought significant changes to various aspects of life, including education. In this digital era, digital literacy has become an essential competence for both teachers and students to adapt to technological developments and face global challenges. Digital literacy is not only limited to the ability to operate digital devices but also involves critical thinking skills in selecting information, ethical behavior in digital interactions, and the ability to use technology to support meaningful and effective learning. This study aims to examine various literature sources related to the development of digital literacy among teachers and students. Through a literature review method, this research analyzes concepts, roles, and strategies for developing digital literacy in education. The findings indicate that digital literacy plays a crucial role in improving teachers' professional competence and preparing students with 21st-century skills, namely Critical Thinking, Creativity, Collaboration, and Communication (4C). However, digital literacy levels among teachers and students are still varied, influenced by factors such as limited access, lack of training, and low awareness of its importance. Therefore, the development of digital literacy must be intensified to create adaptive, productive, and technology-relevant learning environments.